Endovascular Management of Acute Gastrointestinal Bleeding: A Single Center Study of Effectiveness and Clinical Outcomes - Hussain, Mazhar; Shiraz, Mohammad Atif; Amin, Muhammad Umar; Abbas, Ghulam; Haider, Raza Rahim; Akhtar, Sohail (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate the clinical as well as technical success of endovascular management in patients of gastrointestinal bleeding.Study Design: Cross-sectional study.Place and Duration of Study: Armed Forces Institute of Radiology and Imaging, Rawalpindi, Pakistan, from Feb 2023 to Aug 2023.Methodology: A total of 40 patients were enrolled with gastrointestinal bleeding treated with unsuccessful endoscopic management or in which endoscopic management was not possible. Study data was recorded on a predesigned proforma. This procedure involved the injection of small particles or coils into the blood vessels to block blood flow to the tumor, a minimally invasive alternative to surgery to control bleeding or shrink tumors.Results: Duration between angiography and clinical manifestations was 5.92±1.22 days. The pathological angiography was found in 72.5% of patients and embolization in 92.5% of patients. Total technical success was found in 90.0% and clinical success was found in 87.5%. Further, the re-bleeding was noted among 22.5% of patients. Re-bleeding was higher in those having two or more co morbidities.The overall mortality was 27.5%, higher in re-bleeding patients.Conclusion: Endovascular management is a highly safe and effective treatment option for gastrointestinal bleeding that cannot be treated endoscopically. This method has a high technical success rate and a low level of complications, making it suitable for high-risk patients.